2004
DOI: 10.1097/01.hjh.0000133724.16947.a3
|View full text |Cite
|
Sign up to set email alerts
|

CD14 C(−260)T gene polymorphism, circulating soluble CD14 levels and arteriosclerosis

Abstract: Although (C260T) polymorphism in CD14 gene in this study is associated with expression of sCD14, no significant association was found between this polymorphism and early markers of atherosclerosis. This polymorphism affects plasma levels of sCD14 in relation to current smoking status. Further studies are needed to determine whether this interaction influences the deleterious effect of smoking on vascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
(51 reference statements)
1
20
0
1
Order By: Relevance
“…Taking into account the anti-inflammatory role of HDL in reducing CD14 expression [29] and the existence of an interplay among HDL, triglycerides and carotid intimamedia thickness [33,34], these findings seem to indicate a pathogenetic role in the interaction between the genetically determined CD14 hyper-expression and pro-atherogenic lipoprotein profile. Indeed, consistent with the findings from other authors [6,8,15,16,35], patients with TT genotypes displayed a series of altered parameters related to the development and progression of atherosclerosis, such as enhanced plasma concentration of sCD14 and lipid serum profile (low HDL and high triglycerides). Since the number of hypercholesterolemic patients was small, further studies in a larger population will be required to confirm the influence of -260 CD14 polymorphism on HDL cholesterol and triglyceride serum concentrations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Taking into account the anti-inflammatory role of HDL in reducing CD14 expression [29] and the existence of an interplay among HDL, triglycerides and carotid intimamedia thickness [33,34], these findings seem to indicate a pathogenetic role in the interaction between the genetically determined CD14 hyper-expression and pro-atherogenic lipoprotein profile. Indeed, consistent with the findings from other authors [6,8,15,16,35], patients with TT genotypes displayed a series of altered parameters related to the development and progression of atherosclerosis, such as enhanced plasma concentration of sCD14 and lipid serum profile (low HDL and high triglycerides). Since the number of hypercholesterolemic patients was small, further studies in a larger population will be required to confirm the influence of -260 CD14 polymorphism on HDL cholesterol and triglyceride serum concentrations.…”
Section: Discussionsupporting
confidence: 86%
“…TT genotype was found to be associated with a major production of sCD14 both in [15] and carotid stenosis or peripheral atherosclerosis patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…187 Soluble CD14 has been shown to increase cellular responses to LPS both in vivo and in vitro. 188 Inflammatory atherosclerotic disease has been reported to significantly elevate plasma sCD14 concentration and markers of chronic inflammation compared to normal individuals. [189][190][191] Plasma sCD14 concentration has also been linked to the pathophysiology of other inflammatory disease states.…”
Section: Accessory Proteinsmentioning
confidence: 99%
“…However, this result might be modified by smoking, as a significant interaction was observed between smoking and CD14 genotype in sCD14 expression. [16] Our study did not show any significant interaction between smoking and CD14 polymorphism. Another study [14] reported that the CC genotype was associated with an increased cardiovascular mortality in dialysis patients in the subgroup of hypertensive and non-smoking subjects.…”
Section: Discussionmentioning
confidence: 58%